Study of Parameter Influence on Quality on the Electromagnetic Imaging Reconstruction from the Spectrum of the Diffracted Field: Application to Reconstruction of the leakage Current of ISM Applicators - Mejdoub, Y.; Ghammaz, A.; Rouijaa, H.; Senhaji Rhazi, K. (Advanced Electromagnetics, 2019)
The ISM applicators generate leakage currents that can disrupt satellite TV transmission, taking into account the effects of the electromagnetic waves and those of the CEM. We are interested in these as a way to reconstitute their leakage currents, using the Micro-waves Imagery. We propose such a method of spectral analysis, which is intended to reconstruct the equivalent current distribution (position and form) to an object starting from the diffracted field spectrum by the Micro-waves Imagery. Our contribution resides in the influence of different parameters (N number of the measurement point, and the distance z0 of the measurement plane) on the reconstitution quality. This method is presented and illustrated; an algorithm of reconstructing the image of an object existing within a surrounding homogenous medium with known dielectric properties, this algorithm is developed with MATLAB. This method leads to more significant results, and quickly permits to get information about the object form.